Containment of Corona Outbreak Through Lockdown and Social Distancing Among the Community During the Corona Outbreak. - G, SASIPRIYA.; N. P, MURALIDHARAN.; PRIYA, A JOTHI (The journal of contemporary issues in business and government, 2020)
The aim of the study was to determine the compliance of lockdown and social distancing among the community during the corona outbreak. The current outbreak of the novel coronavirus also known as COVID-19. Social distancing The social distancing is carried over generations to minimize the spread of coronavirus by limiting its production rate among communities. Coronavirus is severe acute respiratory syndrome. Social distancing is a non - pharmaceutical infection prevention and control intervention implemented to avoid contact between those who are infected with a disease causing pathogen. It helps in slowing down the rate and extent of disease transmission in a community. In lockdown people are stressful, the secondary workers getting less salary and the economical status is low due to lockdown. The poor people have no job,shortage of food and shelter. Our study contributes to better understanding but compliance of lockdown and social distancing among the community.